2017
DOI: 10.3389/fnhum.2017.00239
|View full text |Cite
|
Sign up to set email alerts
|

Autistic Children Show a Surprising Relationship between Global Visual Perception, Non-Verbal Intelligence and Visual Parvocellular Function, Not Seen in Typically Developing Children

Abstract: Despite much current research into the visual processing style of individuals with Autism Spectrum Disorder (ASD), understanding of the neural mechanisms is lagging, especially with respect to the contributions of the overlapping dichotomies of magnocellular/parvocellular (afferent neural pathways), global/local (perception) and dorsal/ventral (cortical streams). Here, we addressed this deficiency by measuring inspection times (ITs) for novel global/local stimuli as well as recording nonlinear visually evoked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 61 publications
2
20
0
Order By: Relevance
“…For this purpose different authors have used various levels of low-end contrast stimulation, one as low as 1.3%, 38 another 10%, 39 and one as high as 24% Michelson contrast. 40 Our present findings, differentiating pathways using 15% Michelson contrast for low and 85% for high, expand upon our earlier observations published in this journal confirming CNS conservation of complementary bilateral visual function in glaucoma based on VF refined data analysis. 25 , 29 , 30 It now appears that when both magnocellular and parvocellular function cannot be fully supported by either eye, one eye will tend to favor high-speed low-resolution function and the fellow eye will tend to favor lower speed, higher resolution function ( Fig.…”
Section: Discussionsupporting
confidence: 90%
“…For this purpose different authors have used various levels of low-end contrast stimulation, one as low as 1.3%, 38 another 10%, 39 and one as high as 24% Michelson contrast. 40 Our present findings, differentiating pathways using 15% Michelson contrast for low and 85% for high, expand upon our earlier observations published in this journal confirming CNS conservation of complementary bilateral visual function in glaucoma based on VF refined data analysis. 25 , 29 , 30 It now appears that when both magnocellular and parvocellular function cannot be fully supported by either eye, one eye will tend to favor high-speed low-resolution function and the fellow eye will tend to favor lower speed, higher resolution function ( Fig.…”
Section: Discussionsupporting
confidence: 90%
“…This could explain why synaesthetes and individuals with autism excel at visual tasks in which global contexts, involving long-range feedback, have to be ignored. Relatedly, for both synaesthesia [18,20] and autism [56,71,72], atypical responses in the parvocellular visual system have been reported, which is important for processing spatial detail and colours. Hyperresponsivity of the parvocellular system fits with enhanced perception of details in both synaesthesia and autism and the many forms of colour synaesthesias [1].…”
Section: (C) Possible Neural Mechanismsmentioning
confidence: 99%
“…In addition to commonalities in performance on local/ global perceptual tasks, studies into ASD and synaesthesia have found neural similarities related to visual perception, such as enhanced sensitivity of the parvocellular visual pathway (sensitive to fine detail and high contrast) (see Brown and Crewther 2017;Sutherland and Crewther 2010;Jackson et al 2013 for ASD, andBarnett et al 2008;Van Leeuwen et al 2013 for synaesthesia), as well as increased local and decreased global cortical connectivity (see Just et al 2012 for ASD, andHänggi et al 2011, for synaesthesia). These studies provide suggestions for the neural mechanisms that might underlie a shared local bias.…”
Section: Evidence For a Local Bias From The Asd And Synaesthesia Resementioning
confidence: 99%